Properties of red sandstone-limestone-cement ternary composites: Hydration mechanism, microstructure, and high-temperature damage - Weichuan Zhang; Mingxian Zhao; Zhongyan Yang; Rongxin Guo; Xiao-Yong Wang; Run-Sheng Lin (Developments in the Built Environment, 2024)
A significant amount of waste is generated during the sandstone mining process. This study explores the use of red sandstone waste as a supplementary cementitious material to address environmental concerns in cement production. The experimental methods include isothermal calorimetry, compressive strength testing, thermogravimetric analysis, X-ray diffraction, infrared spectroscopy, scanning electron microscopy, high-temperature damage testing (200, 600, and 900 °C), and mesoscopic image analysis. The experimental findings reveal the following: (1) Red sandstone powder enhanced cement hydration and optimized the samples' microstructure. (2) There is no significant difference in the effects of calcined and uncalcined red sandstone powders at 800 °C. (3) At 200 °C, the high-temperature damage of the samples containing red sandstone and limestone powders was reduced. This study is expected to positively impact the utilization of red sandstone waste and contribute to the reduction of carbon emissions in cement production.